Evaluation of immunoglobulin replacement therapy in secondary immunodeficiency at three British Columbia hospitals. Issue 4 (30th January 2023) - Tran, Ann; Marcon, Krista; Zamar, David; Mi, Jian; Shad, Jodi; Zheng, Joey; Nicolson, Hamish; Onell, Rodrigo; Shih, Andrew W.
Abstract: Background and Objectives: Immunoglobulin (Ig) usage has ongoing shortage concerns. Secondary immunodeficiencies (SIDs) account for a major proportion of usage of Igs in Canada. We audited Ig usage in patients with SID at three British Columbia hospitals to determine whether more stringent local guidelines are necessary. Materials and Methods: A retrospective chart review was performed for patients who had Ig ordered between 1 January 2018 and 31 December 2019 for any SID indication. Cohorts were stratified into chronic and new users, and the Australian BloodSTAR guidelines were used as the benchmark at the time of conception. Having an eligible primary diagnosis, meeting SID criteria, an appropriate dosage and follow‐up immunoglobulin G (IgG) levels encompassed appropriate usage. Results: There were no demographic differences between chronic ( N = 81) and new ( N = 33) cohorts. The new cohort had a higher rate of appropriate usage (45.7% vs. 66.7%, p = 0.06). The most common reason for inappropriate usage in both groups was the lack of follow‐up IgG level at 6 or 12 months. Factors, displayed by relative risk (RR), associated with appropriateness included the dispensing hospital (RR: 6.60), use of subcutaneous Ig (RR: 3.84), having an IgG level before starting therapy (RR: 3.51) and documentation of clinical benefit (RR: 4.70). Conclusion: There are high rates of inappropriate Ig usage in SID patients in both new and chronically treated groups. More stringent local guidelines and processes for assessing initial and ongoing Ig replacement are warranted.